Analisis Gaya Bahasa Senryuu dalam Anime “Senryuu Shoujo” Karya Masakuni Igarashi - Jovan Dzulfikar Pranata; Eva Amalijah (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2023)
Abstract. Language is an arbitrary system of voice symbols used by members of social groups to collaborate, communicate and identify. Style of language is part of language. Language style is the way that the author expresses their ideas in accordance with the purpose and outcome they wants to achieve. This study of the language style analyzed Masakuni Igarashi's